(untitled) (Journal of Civil Engineering Researchers, 2024)
Sinkholes pose significant risks to infrastructure, requiring detailed investigation and effective repair strategies. This paper details a case study of a persistent sinkhole along a driveway in Nashville, Tennessee, which has caused repeated pavement subsidence despite multiple repairs. The investigation included site visits, drilling operations, soil and rock analysis, and groundwater assessment. Three mitigation approaches were evaluated including conventional inverted rock filter repair, constructing a land bridge, and compaction grouting. After considering technical, situational, and cost factors, compaction grouting was chosen as the optimal solution. The paper outlines the compaction grouting repair strategy, including methodology, materials, and construction specifications. The findings aim to enhance design standards and construction practices for sinkhole repairs in Tennessee and similar geotechnical regions.